Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ejlt.201900302
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reaction Kinetics of Edible Oil Oxidation at Ambient Temperature by FTIR Spectroscopy

Abstract: Edible oils are studied to analyze their reaction kinetics during oxidation and predict shelf life at ambient temperature. Rapeseed oil (RO), soybean oil (SO), linseed oil (LO), and peanut oil (PO) are detected via Fourier transform infrared spectroscopy with a mesh cell as spectral acquisition accessory. The reaction kinetics of ROOH bonds, C═O bonds, trans double bonds (TDBs), and carbon chain skeletons (CCSs) are determined by absorbance changes in their characteristic absorption peaks. Prediction models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…It is observed that th It needs to be noted that the low intensity of the bands in the 900-700 cm −1 region and the overlap with that at 723 cm −1 for the S-300 sample made it impossible to estimate the DOC, and therefore, this solid is not considered in Figure 6. It is observed that the DOC of the PAH increases up to ~500 • C, which is in good agreement with the data in the literature [18,32], but at T > 500 • C, the DOC strongly decreases, contrarily to what was expected. It was supposed that this effect was caused by the presence of inorganic salts in the raw material, and experiments that were designed to confirm this point were carried out.…”
Section: Atr-ftir Analysis: the Effect Of Temperaturesupporting
confidence: 92%
See 3 more Smart Citations
“…It is observed that th It needs to be noted that the low intensity of the bands in the 900-700 cm −1 region and the overlap with that at 723 cm −1 for the S-300 sample made it impossible to estimate the DOC, and therefore, this solid is not considered in Figure 6. It is observed that the DOC of the PAH increases up to ~500 • C, which is in good agreement with the data in the literature [18,32], but at T > 500 • C, the DOC strongly decreases, contrarily to what was expected. It was supposed that this effect was caused by the presence of inorganic salts in the raw material, and experiments that were designed to confirm this point were carried out.…”
Section: Atr-ftir Analysis: the Effect Of Temperaturesupporting
confidence: 92%
“…The DOC calculated as a function of the temperature (black line in Figure 6) increases to 500 °C and decreases for higher temperatures, contrarily to the data reported in the literature [32]. The observed trend suggests that the cracking reaction (1) occurs at T > 500 °C, but the condensation reactions seem to be limited.…”
Section: Doc) Highsupporting
confidence: 73%
See 2 more Smart Citations
“…Therefore, the data before the reaction stabilizes in Figure 4 are fitted by substituting the equation in Table 3 and the fitting results are shown in Figures 5 , 6 . The kinetic fitting model is considered to be well fitted when the correlation coefficient ( R 2 ) is greater than 0.85 ( Wang et al, 2020 ; Li et al, 2023a ), which shows that the R 2 between the internal diffusion Equation (1) + 2(1 – r) – 3(1 – r) 2/3 and time t is greater than 0.85 for different acid-slag ratios, acidolysis temperatures and TBFS particle sizes. It can be assumed that the acidolysis reaction rate is mainly controlled by the internal diffusion of H 2 SO 4 in the product layer ( Zhang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%